Study on Sedation with Local Analgesia in Calves - Sarker, NC; Hashim, MA; Ray, BP; Sarker, SK (ANIMAL PRODUCTION, 2011)
Abstract. The effect of sedatives and analgesics on heart rate, respiration rate and rectal temperature were observed. Heart rate and respiration rate significantly decreased during sedation with xylazine hydrochloride plus 2% lignocaine hydrochloride or 0.5% bupivacaine hydrochloride. A significantly decreased heart rate and respiration rate also found during sedation with diazepam plus 2% lignocaine hydrochloride or 0.5% bupivacaine hydrochloride. Two percent lignocaine hydrochloride showed short onset, rapid spreading and no side effect. Duration of analgesia was longer with 0.5 % bupivacaine hydrochloride (55.88±1.58 min in Group B and 48±11.25 min in Group D) compared to 2% lignocaine hydrochloride (39.60±5.77 min in Group A and 43.6±5.81 min in Group C). Xylazine hydrochloride showed short onset and long duration of sedation compared to diazepam. So for herniorraphy, xylazine hydrochloride can be used as a better sedative while 0.5 % bupivacaine hydrochloride can be used as a local analgesic for longer duration of action.Key Words: lignocaine hydrochloride, sedation, analgesiaNC Sarker et al/Animal Production 13(3):191-197 (2011)